2001
DOI: 10.1063/1.1412284
|View full text |Cite
|
Sign up to set email alerts
|

Thermal stability and diffusion in gadolinium silicate gate dielectric films

Abstract: Access and use of this website and the material on it are subject to the Terms and Conditions set forth at Thermal stability and diffusion in gadolinium silicate gate dielectric films Landheer, D.; Wu, X.; Morais, J.; Baumvol, I. J. R.; Pezzi, R. P.; Miotti, L.; Lennard, W. N.; Kim, J. K.http://nparc.cisti-icist.nrc-cnrc.gc.ca/npsi/jsp/nparc_cp.jsp?lang=fr L'accès à ce site Web et l'utilisation de son contenu sont assujettis aux conditions présentées dans le site LISEZ CES CONDITIONS ATTENTIVEMENT AVANT D'UTIL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
14
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 19 publications
2
14
0
Order By: Relevance
“…O 2 annealing for 60 s ͑sample 3 in Table I͒ produces an increase on the O-areal density of about 30% with respect to the as-prepared sample ͑sample 1͒ and a comparable percentage decrease on the N-areal density. Figure 1͑b͒ shows Si, 16 [9][10][11][12][13] in aluminum, zirconium, and gadolinium oxides and silicates, the present HfO 2 /SiO x N y structure displays higher resistance to oxygen migration from the gas into the solid phase and incorporation therein, as well as smaller isotopic exchanges. 29 Si profiles were determined by NRP 16 ͑results not shown here͒, revealing that Si remains immobile during annealing, in contrast to several of the earlier mentioned materials where substrate Si is seen to migrate into the oxide film.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…O 2 annealing for 60 s ͑sample 3 in Table I͒ produces an increase on the O-areal density of about 30% with respect to the as-prepared sample ͑sample 1͒ and a comparable percentage decrease on the N-areal density. Figure 1͑b͒ shows Si, 16 [9][10][11][12][13] in aluminum, zirconium, and gadolinium oxides and silicates, the present HfO 2 /SiO x N y structure displays higher resistance to oxygen migration from the gas into the solid phase and incorporation therein, as well as smaller isotopic exchanges. 29 Si profiles were determined by NRP 16 ͑results not shown here͒, revealing that Si remains immobile during annealing, in contrast to several of the earlier mentioned materials where substrate Si is seen to migrate into the oxide film.…”
mentioning
confidence: 96%
“…Previous studies 1 in other high-k ultrathin films on Si indicated that the interface layer thickness and composition can vary according to the deposition method and routine, and various species can be transported during post deposition thermal processing, like oxygen, 9,10 Si, [11][12][13] and the metal species, 14,15 altering the atomic concentrations as well as chemical composition of the system and consequently electrical characteristics like dielectric constant, interface density of states, and mobility of charge carriers in the transistor channel. In particular, stability against annealing in O 2 -containing atmospheres is of high interest, since in further processing steps it is either performed intentionally to improve leakage current and CET characteristics 1,7,8 or unintentionally, because oxygen is almost always residual in any production furnace.…”
mentioning
confidence: 99%
“…8,9 Gd 2 O 3 layers on strained Si x Ge 1−x were found to be most effective for surface passivation of SiGe giving the lowest interface state density. Landheer et al 10 showed that oxygen diffused into the film, thereby eliminating oxygen vacancies during O 2 annealing. In this letter, a high-k gadolinium oxide gate dielectric was grown on Si substrate by reactive rf sputtering.…”
mentioning
confidence: 99%
“…The formation of SiO 2 is likely the result of oxygen from the annealing atmosphere diffusing into the interfacial region through the gadolinium silicate layer and reacting with the silicon to form SiO 2 . Oxygen diffusion through the gadolinium silicate ®lm has been assessed by Rutherford backscattering and narrow resonance nuclear pro®ling and reported elsewhere [8].…”
Section: Resultsmentioning
confidence: 99%